Methylmercury in lake bed soils during re-flooding of an Appalachian reservoir in the northeastern USA. (27th August 2021) - Eklöf, Karin; Drohan, Patrick; Needoba, Joseph; Landefeld, Sally; Peterson, Tawnya D; Hu, Haiyan; Iavorivska, Lidiia; Boyer, Elizabeth W
Abstract: Mercury methylation, where inorganic mercury (Hg) is converted to methylmercury (MeHg), can increase in soils when flooded. While effects of the initial flooding of soils on MeHg production have been well studied, less is known about impacts of re-flooding on MeHg production. Lake Perez, an impounded recreational reservoir in the Appalachian Highlands, was completely drained then re-filled 7 years later. We use a combination of chemical, soil physical, and microbial data to quantify changes in MeHg before and after re-flooding of the lakebed. Portions that were transiently saturated due to pluvial flooding had the highest pre-flooded MeHg concentrations. When the lake was re-flooded, concentrations of MeHg in subaqueous soils increased by a factor of 2.74 (+174%) on average. Substantial variability was observed among the sampling sites, with smaller increases in MeHg at sites subjected to seasonal flooding during periods when the reservoir was drained. The increase of soil MeHg after re-flooding was lower in this study compared to studies that evaluated soil MeHg after initial flooding, indicating that re-flooding of a former lake bed caused a smaller response in MeHg production compared to initial flooding of terrestrial land. This study advances understanding of the environmental impact of impounded reservoirs.